Evaluation of Amlodipine Use Among Geriatric Patients at Mojogedang I Community Health Center, Karanganyar - Hapsari, Eliza; Adiningsih, Retnowati (Pustaka Media Publishing, 2026)
Evaluation of Amlodipine use in geriatric patients is important because this age group often experiences pharmacokinetic and pharmacodynamic changes that increase the risk of side effects. Amlodipine is effective in controlling hypertension, but geriatric patients with comorbidities such as kidney disease or those taking multiple medications are vulnerable to drug interactions that exacerbate side effects. This study aims to evaluate the use of Amlodipine and provide a realistic picture of the quality of Amlodipine use in geriatric patients. This is a non-experimental descriptive study with retrospective data collection using medical records in the Community Health Center Management Information System (SIMPUS). The sample was selected using purposive sampling that met the inclusion and exclusion criteria. An evaluation of Amlodipine use was then conducted based on the indicators of appropriate patient, appropriate drug, and appropriate dose, in accordance with the JNC VIII guidelines. Among the 46 patients evaluated, 100% fulfilled the criteria for appropriate patient selection and appropriate drug use, while 97.83% met the criterion for appropriate dosage. A dosage inaccuracy rate of 2.17% was identified, highlighting the need for increased attention to dosage determination in geriatric patients. The use of Amlodipine in geriatric patients does not yet fully comply with the JNC VIII guidelines; therefore, periodic evaluation of medication use remains necessary to ensure optimal and safe therapy for geriatric patients.